Integrating Artificial Intelligence into Adaptive Learning Worksheets: a Community Service Initiative to Support Urban Food Security - Apit Fathurohman; Esti Susiloningsih; Hilda Agustina; Primayoga Harsana Setyaaji (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of artificial intelligence (AI) requires teachers to adapt in designing more innovative and contextual learning. However, most partner school teachers still face challenges in utilizing AI-based technology to develop effective teaching materials. This community service program aimed to enhance teachers’ capacity in developing adaptive AI-based student worksheets (LKPD) that support differentiated learning. The implementation consisted of socialization, training, practical mentoring, and feedback evaluation, involving 25 elementary school teachers. The results showed a significant improvement in teachers’ ability to use AI tools such as ChatGPT, Canva AI, and Quizizz AI to design interactive and contextual LKPD. Participant satisfaction surveys indicated that 72% rated the activity as very good and 28% as good. This program effectively improved teachers’ digital literacy and fostered creative integration of technology into classroom learning.